Understanding international migrations in rural areas: New processes of social innovation and rural regeneration in Southern Italy - Karen Urso (Italian Review of Agricultural Economics (REA), 2021)
The current international migration has transformed the morphology, the social structures and the local economies in many rural areas, often helping to reverse a long-term demographic and social decline. Analyzing two experiences of Southern Italy, affected by depopulation and deficit of social services, the paper aims to explore how immigrants can contribute to social regeneration, focusing on the hypothesis of social innovation. The strengthening of local services and the diversification of economic activities, which are conveyed by immigration, have helped to achieve significant implications for the territories. On the one hand the positive impact of migration for rural regeneration is recognized, on the other the settlement of new population appears problematic, due to the resistance processes posed by local communities and the lack of social infrastructures. These could represent an obstacle to the possibility of social change.
Keywords: F22; O35; P25; 330; international migration; rural areas; rural regeneration; social innovation; Southern Italy